MENINGKATKAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI MELALUI MEDIA LINGKUNGAN PADA SISWA KELAS IV DI SDN 3 BONGOMEME KABUPATEN GORONTALO - Miranda Maksum; Rusmin Husain; Wiwy T. Pulukadang; Fidyawati Monoarfa; Sukri Katili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve descriptive essay writing skills among fourth-grade students at SDN 3 Bongomeme, Gorontalo Regency, by utilizing the surrounding environment as a learning medium. This study employed a classroom action research design conducted in two cycles. Data collection techniques included tests, observation, and documentation. The implementation process consisted of four stages: planning, action, observation and evaluation, analysis, and reflection. The subjects were 14 fourth-grade students at SDN 3 Bongomeme. The observation results indicated that the students’ descriptive essay writing skills were initially low. Of the 14 students, only 2 students (14%) demonstrated adequate ability, while 12 students (86%) had not yet achieved the expected competence. In Cycle I, Meeting I, only 4 students (28%) were able to write a descriptive essay, which increased to 9 students (64%) in Meeting II. In Cycle II, Meeting I, a significant improvement was observed, with 12 students (86%) successfully writing a descriptive essay using the surrounding environment as a learning medium. Therefore, it can be concluded that the descriptive essay writing skills of fourth-grade students at SDN 3 Bongomeme, Gorontalo Regency, improved significantly.